SERANGAN HAMA KUDIS PISANG Nacoleia octasema Meyr (LEPIDOPTERA: PYRALIDAE) PADA BEBERAPA KULTIVAR PISANG - Supriyadi Supriyadi; Yuanita Wahyu Hapsari; Retno Bandriyati Arni Putri; Retno Wijayanti (Jurnal Agroteknologi, 2022)
Banana (Musa sp.) is a fruit plant that commonly cultivated in the tropics.  Indonesia has a variety of banana cultivars, each cultivar may a different susceptibility to pests and diseases. This study aims to identify the damage intensity of banana scab moth (Nacoleia octasema Meyrick) on some banana cultivars. The Survey was conducted on banana plantation, while the sample was selected using random sampling. Six banana cultivars were observed, namely Kepok, Raja Nangka, Raja Bulu, Raja Tawi and Mas Kirana. The research variables were the damage intensity of banana scab moth and the physical character of the fruit. The damage intensity recorded the bananas fruit showing the symptoms of scab moth. The result were analyzed by using t test and presented in table or/ and graph. The results showed that the damage of banana scab moth was recorded on all banana cultivars. So, there were not banana cultivars absolutely resistant to N. octasema. The cultivars of Kepok and Raja Nangka were preferred, while Mas Kirana was less preferred by N. octasema. The attack of N. octasema larvae began from the first hand position, whila the highest damage was recorded in the last hand position of banana bunch. The damage intensity of N. octasema on the lowerside of each hand position of banana bunch was significantly higher than the upperside, that even no damage